Mediation Effect of Work Motivation on Relationship of Soft Skill and Hard Skill on Employee Performance in Denpasar Marthalia Skincare Clinical - I Gusti Bagus Sindu Martha Nugraha; Ni Wayan Sitiari; Putu Ngurah Suyatna Yasa (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
Employee motivation is a reflection of the level of energy, commitment, and creativity possessed by employees used to work. This study aims to determine the effect of soft skills and hard skills on employee performance with work motivation as a mediating variable in the Clinical Marthalia Skincare Denpasar. The population in this study were all employees who worked at Marthalia Skincare Clinic in 2019. The sampling method used in this study was the census method, thus, the number of samples in this study was 32 employees of the Marthalia Skincare Clinic in Denpasar. The research data is primary data that are the results of questionnaire data given to employees of the Marthalia Skincare Clinic Denpasar. Testing the hypothesis of this study using Structural Equation Modeling (SEM) analysis with the Partial Least Square (PLS) approach. The results showed that: (1) Soft Skill had a positive effect on work motivation. (2) Hard Skill has a positive effect on work motivation. (3) Soft Skill has a positive effect on employee performance. (4) Hard Skill has a positive effect on performance. (5) Work motivation has a positive effect on performance. (6) motivation is a partial mediation between soft skills and performance. (7) work motivation is not a mediation between hard skills and performance. It is recommended to further researchers to examine other mediating variables that affect the relationship between hard skills and employee performance.